The role of venture capital funds in dissemination and development of innovation in Canada - Marat Ressin (Journal of Innovation and Entrepreneurship)
Abstract The aim of this study was to determine the role of venture capital funds in promoting innovative development in Canada and to identify regional features of their effectiveness in developing recommendations for optimizing the venture and innovation ecosystem. The subject matter of the research was limited to an analysis of the activities of Venture Capital Funds affiliated with accelerators. The research methodology is based on calculations of business survival rates, patent approval rates, and overall venture activity for each province in Canada. Data were collected from various sources, including Canadian statistical databases and venture fund reports. Correlation analysis methods were applied to identify dependencies between venture and innovation indicators. To assess regional success, both quantitative (investment volume, patent number) and qualitative parameters (startup survival rates) were used. The results of the study demonstrate a close relationship between the volume of venture capital deals and innovation activity. The analysis revealed a significant concentration of venture capital in the largest provinces of the country (Ontario, Quebec, British Columbia, and Alberta), which leads to regional imbalances and limits the potential of less developed regions. Based on statistical data, key barriers to developing the innovation potential of peripheral provinces were identified, including insufficient support for innovative activities, weak links between patent activity and financing, and limited access to acceleration infrastructure. The study presents recommendations for creating conditions that could ensure the redistribution of financial flows and open prospects for the development of innovative projects in less developed provinces, accelerate the commercialization of promising technologies, and increase the overall sustainability of startups implementing such projects.